Pricing of Sovereign Credit Risk : Evidence From Advanced Economies During the Financial Crisis - Alper, Emre (IMF Working Papers; Working Paper ;, 2012)
We investigate the pricing of sovereign credit risk over the period 2008-2010 for selected advanced economies by examining two widely-used indicators: sovereign credit default swap (CDS) and relative asset swap (RAS) spreads. Cointegration analysis suggests the existence of an imperfect market arbitrage relationship between the cash (RAS) and the derivatives (CDS) markets, with price discovery taking place in the latter. Likewise, panel regressions aimed at uncovering the fundamental drivers of the two indicators show that the CDS market, although less liquid, has provided a better signal for sovereign credit risk during the period of the recent financial crisis.